Risk of recurrent thromboembolic events according to treatment duration in patients with superficial vein thrombosis treated with intermediate dose of tinzaparin. (April 2023) - Karathanos, Christos; Kakkos, Stavros K; Georgiadis, Georgios; Ioannou, Christos; Vasdekis, Spyros; Chatzis, Dimitrios; Latzios, Panagiotis; Giannoukas, Athanasios D; ,
Objectives: To evaluate the risk of symptomatic venous thromboembolism (VTE) recurrence at 3 months in relation to treatment duration, according to baseline risk factor profiles, in patients with superficial vein thrombosis (SVT) treated with intermediate dose of tinzaparin. Methods: We performed a pooled analysis on individual data from two prospective studies designed to assess the efficacy and safety of tinzaparin in intermediate dose (131 IU/kg) in patients with SVT. Treatment duration was at the treating physician's discretion. All patients were followed up for at least 3 months. Results: A total of 956 patients (65% female, mean age 58.7 ± 13.7 years) were included. The median treatment duration was 30 days (range, 3–200 days). History of deep vein thrombosis (DVT), location of SVT above the knee, and palpable induration were the only independent factors associated with prolonged treatment duration. During follow-up, 95.9% of patients were event free. Outcomes-related adverse events occurred in 39 (4.1%) patients and their median duration of treatment was 33 days (range, 7–200 days). Recurrent VTE events occurred in 33 patients, including 22 cases of SVT recurrence, 8 cases of DVT, and 1 case of pulmonary embolism. The median time to the event was 29 (6–113) days. Recurrent thromboembolic events were not related to treatment duration as occurred in 17 patients (51.5%) treated up to 30 days and in 16 patients (48.8%) received prolong treatment ( p = .46). Length of thrombus at the index event was significantly associated with higher risk for VTE recurrence. Conclusions: Intermediate dose of tinzaparin for 30 days is an effective and safe treatment for SVT. The risk of recurrent VTE events may be higher in patients with greater amount of thrombus at index event.